CORRELATION OF METABOLIC SYNDROME WITH GENU OSTEOARTHRITIS IN TYPE 2 DIABETES MELLITUS PATIENTS - Diaz Syafrie Abdillah; Ardyarini Dyah Savitri; Effendi . (Universitas Airlangga, 2022)
AbstractIntroduction: Osteoarthitisgenu is a joint disorder of the genu section due to a gradual decrease in cartilage bone cohesiveness. A metabolic syndrome is a group of both lipid and non-lipid abnormalities in an individual. This study aims to determine the relationship between metabolic syndrome and the incidence of osteoarthritis genu in type 2 DM patients at RSI Jemursari Surabaya.Methods: This study uses an analytic observational method with a cross-sectional design. The population of type 2 DM patients and samples were obtained according to the inclusion and exclusion criteria. The sample size is 98 samples with a simple random sampling technique.Result: In this study, the frequency of the metabolic syndrome in this study (31.6%), age 55-65 years (38.7%), male gender (51.6%), and components of the metabolic syndrome include hypertension, type 2 diabetes, hypertriglyceridemia (83.9%). On the frequency of Genu Osteoarthritis (28.6%) with the age of 46-55 years (43%), female gender (61%). Osteoarthritis genu location distribution is mostly bilateral (60.7%). Conclusion: Based on the results of the Chi-Square Test statistical test using the SPSS statistical application, it shows a p significance value of 0.080 (> 0,05). Keywords: Metabolic syndrome, Osteoarthritis genu, DM type 2